Effectiveness of Learning Models Contextual Teaching And Learning In Increasing Religious Cognitive Competence in Institutions Pesantren Modern Muadalah - Taufik Rizki Sista; Agus Budiman (At-Ta'dib, 2020)
The research was conducted at Muadalah Islamic Boarding School which in this case was Darussalam Gontor Modern Islamic Boarding School branch 2. Researchers conducted research on the Effectiveness of the Contextual Teaching Learning Learning Model on religious lessons. Gontor's modern cottage was chosen because it is possible to practice CTL teaching model in class, so that the research objectives can be achieved. The general objective of this research is to know the experimental learning patterns by using the Contextual Teaching and Learning method in Gontor boarding schools, knowing the effectiveness of the Contextual Teachng Learning learning model in improving understanding of religious material in Muadalah Modern Islamic boarding schools. The initial stages of this research will be carried out by field observations. Then proceed with class grouping into two groups, groups A and B. Group A is a control group that is not given experimental treatment. The next stage is to carry out treatment by giving learning with the CTL model on object B. The final stage is a post test aimed at finding out the effectiveness of the religious learning model at the institution. The method used is a quantitative method, with the type of experimental research. The population in the design of this study were all 4 KMI students or equivalent with 1st grade of high school. Presentation of data is done by a combination among qualitative and quantitative method. Qualitative methods are intended to describe the details of learning activities with the CTL model, while the quantitative method is used to present the results of the post test validity. The specific targets of this research are 1) to find out how students' cognitive competence in the religious field before treatment 2) to find out the effectiveness of the contextual teaching learning model. The results of this study found that the significance of the calculation of the free sample t test with SPSS was 0,000 <0.05, with the conclusion that the CTL method was effectively implemented on religious lessons in Muadalah Islamic boarding schools.